Evaluación de la eficacia de tres métodos de diagnóstico complementario sobre los niveles de glucosa en caninos domésticos - Garcia Buenaño, Ana Karina (2025)
Glucose measurement makes it possible to determine the medical status of a patient affected by diseases such as Diabetes Mellitus, which is very common in dogs. In this research, carried out at the HOSPIVET veterinary hospital, located in the Chimborazo Province, Riobamba Canton, an evaluation was carried out of the efficacy of three complementary diagnostic methods on glucose levels in domestic canines. The objectives were: to evaluate the efficacy of three complementary diagnostic methods on glucose levels in domestic canines; To compare the accuracy of each complementary diagnostic method in measuring glucose levels in dogs, identify potential factors that could influence the results of the different assessment methods, such as the weight, age, and breed of the dogs, as well as their diet and physical activity, and compare the results obtained with each method with a reference standard (blood chemistry). To verify their accuracy and precision, 60 dogs of different breeds and sexes were sampled. The descriptive method was used, taking into account study factors such as sex, breed, age, weight, sterilization status, and diet. A fasting blood sample was taken for analysis. The results showed that wet chemistry had the highest accuracy, with a mean of 88.45 mg/dL, while the veterinary and human glucometers recorded means of 80.48 mg/dL and 75.95 mg/dL, respectively. Variability in results was associated with factors such as diet type, sterilization status, and breed. The study concludes that although portable glucometers are practical for home monitoring, wet chemistry remains the most reliable reference method in clinical settings due to its higher accuracy and lower variability.